Ageing and place : perspectives, policy, practice - Andrews, Gavin J., 1970-; Phillips, David R. (Routledge studies in human geography, 2005)
An increasing amount of academic research has focused on older people with a particular emphasis on settings, places and spaces. This book provides a comprehensive review of research and the policy area of 'ageing and place'.